Impact Of Global Organization Culture With Reference To Manufacturing Companies In Southeast Asia - Lokhande, Mayur (Digital Repository of Theses, 2025)
A global organization brings in a lot of cultural challenges to the global workforce. Working with cross-functional teams in matrix organization and interacting with different nationalities is part of day-to-day working life in Multinational companies. Overseas assignments, business visits, and cross-border projects are increasing as the development develops. The workforce in global organizations needs to have a global mindset by understanding the cultural dimensions of various geographies to be successful in their roles. However, it’s not easy to understand cultural dimensions. Global culture impacts your day-to-day business. Broader perspective, we can categorize global MNCs into three: Western, European, and Asian companies. For these studies, the focus of research is limited to the appliance industries of India, China, and Thailand. The study aims at identifying various challenges due to the cultural impact of Global culture on the workforce in Southeast Asia countries, especially the companies that are headquartered in Western or European countries. The research aims to understand the cultural challenges in organizations and their impact, the adoptability, and the inclusions. The research aims to propose solutions to improve cultural inclusivity and global collaboration to help the workforce in multinational companies to be successful. The study will also include how India, China, and Thailand adopt and handle the cultural challenges, and study which country is more adaptive and sensitive towards cultural inclusivity and collaboration. The study will cover any previous research on Global Culture and its impact, the research gaps. A questionnaire will be shared with professionals working in of appliances domain in India, China, and Thailand. Interviews will be conducted. Dala analysis by various methods will be carried out. In conclusion, the study shall help organizations to understand cultural challenges, their impact, suggestions on cultural inclusion, and how organizations can improve in this area. It will also help professionals working in MNCs to understand how to understand cultural dimensions and collaborate better in a global environment.